7a+6-3a+9=

Simple and best practice solution for 7a+6-3a+9= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7a+6-3a+9= equation:


Simplifying
7a + 6 + -3a + 9 = 0

Reorder the terms:
6 + 9 + 7a + -3a = 0

Combine like terms: 6 + 9 = 15
15 + 7a + -3a = 0

Combine like terms: 7a + -3a = 4a
15 + 4a = 0

Solving
15 + 4a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + 4a = 0 + -15

Combine like terms: 15 + -15 = 0
0 + 4a = 0 + -15
4a = 0 + -15

Combine like terms: 0 + -15 = -15
4a = -15

Divide each side by '4'.
a = -3.75

Simplifying
a = -3.75

See similar equations:

| 3m+2-3(m+1)=-(-7m+4) | | 15t+17=a-15 | | 6x-30=4 | | -341=15n | | 8-4x=13-5x | | 6+3n-2x-2= | | s+2(s+3)+(4s+-5)=148 | | 9x-4(2x+5)=-15 | | 2x+2(2x-1)=40 | | 5x-6-7x=-x-7 | | n=n*2-n | | 5b+2b-3-2b+7= | | 2(3x-4)+7=3x-2(x+1) | | 5(x+4)-4x=16 | | 3x(2a-2)-7= | | 7x+5b-4x-2b= | | s-2(s+3)+(4s-5)=148 | | 19c-9c= | | 9x-1(6x+3)=6 | | -3-7=6x+6-5x | | 8a+3x-5a+x= | | y/1.56=x | | n+0.1n+1.1=(n-1.5) | | s+5/2+10=38 | | 7+4=3r+6-2r | | 8x(2x+7)=-24 | | -9c-3+8c=22 | | X^2+14=-86 | | 9n+4a-6n-2a= | | 25=-5w | | e=2d+4p | | 9/-3+m=10 |

Equations solver categories